Large deletions of the APC gene in 15% of mutation‐negative patients with classical polyposis (FAP): A Belgian study - G Michils; Sabine Tejpar; Ronald Thoelen; Eric Van Cutsem; Joris Vermeesch; Jean‐Pierre Fryns; Eric Legius; Gert Matthijs (2005)
Germline mutations of the APC gene are responsible for familial adenomatous polyposis (FAP). Most of the mutations are protein truncating mutations and are spread over the coding region. Rare whole-gene deletions or exonic deletions have been described. From a series of 85 patients clinically diagnosed with FAP or attenuated FAP (AAPC) in our center, 30 (35%) were found to have truncating or missense mutations. We have now screened the remaining 55 patients for exonic deletions or duplications, first by semi-quantitative PCR and later by multiplex ligation-dependent probe amplification (MLPA). Three whole-gene deletions and one exon 14 deletion were found (5% of patients). The whole-gene deletions were confirmed by fluorescence in situ hybridization (FISH) analysis, and the breakpoints of the exon 14 deletion could be determined using long range PCR. Further characterization of the whole gene deletions was performed using extragenic polymorphic markers and/or semi-quantitative PCR. We could demonstrate that the deletions do not encompass the MCC gene. Interestingly, the phenotype of the deletion patients was not different from that of patients with truncating mutations. The polyp numbers ranged from attenuated to profuse polyposis and the interfamilial variability of disease phenotype was as in other FAP families. In none of the 28 AAPC patients included in this study, was a large deletion found, while 15% of the patients with classical polyposis had a genomic deletion. It corroborates recently published data, suggesting that large deletions may occur with a frequency higher than 10% in mutation-negative patients with a classical polyposis. In this article, we have included an overview of genomic rearrangements in the 5q21 region.